Analisis penggunaan media pembelajaran ditinjau dari perspektif self directed learning (SDL) di kelas IV sekolah dasar - Isna Imroatul Latifah; Karsono Karsono; Siti Wahyuningsih (Universitas Sebelas Maret, 2023)
The pandemic of Covid-19 has led to school closures and Distance Learning. SD Negeri Kadiluwih Magelang is one of the Distance Learning implementers. With the introduction of PJJ, students are required to learn independently during the learning process, learning media are not used, students become less involved, and students continue to depend on parents and teachers. This study aims to examine the use of instructional media in grade IV SD Negeri Kadiluwih from the self-directed learning (SDL) perspective. This research is descriptive qualitative research. The results of the research are: (1) the learning process at SD Negeri Kadiluwih has attempted to apply student-centered learning by providing opportunities for students to develop themselves; (2) the application of learning media is adjusted based on the needs of students and the material to be delivered by; and (3) the self-directed learning that has been carried out has not fully delivered good results, because there are indicators that have not been fulfilled, i.e., a) students have not dared to create autonomous decisions; b) students do not dare to express their opinions and ideas independently; c) students are not fully planning and preparing their learning media; d) students still have difficulty completing the challenges delivered by the teacher; e) students are comfortable with traditional and systematic learning, and f) students cannot determine the learning media that will be used.